Safety certification -- a path to job security and personal growth. - Budde SR (AAOHN Journal, 2009)
In 2005, the American Board for Occupational Health Nurses, Inc. introduced a new credential in safety management for certified occupational health nurses. To date, 11 nurses have attained this credential and several of those have advanced to the Certified Safety Professional designation. This article discusses the certification process and its benefits. It also discusses problems in the application process observed by the administrators, and offers suggestions to prepare for the examination. Nurses who have attained the Safety Manager credential were surveyed for advice to those considering certification.